A solution for joint pain and body relief through portable exercise machine. (22nd June 2022) - Hasan, Zahir; Kamli, Moath Ali
It is necessity to manufacture a portable machine for exercise at home to keep the body fit. This is particularly required for senior citizens and those having tight schedule or due to some reasons, like COVID-19 pandemic etc. cannot go to the gym. To meet the demand, a portable dual seating light weight exercise machine has been designed and fabricated to cure joint and body pain, which is currently not available in the market. Two persons can exercise on it at a time. On regular exercise with this machine, good results can be obtained to get relief in body as well as to cure joint pain. The machine is economical, and offers a complete range of exercises with easy maintenance. It can also be used as a small table while not in use. In this paper the design approach/methodology is presented first, and then the working principle of the machine is explained, followed by the discussion and conclusion.